Anti-adhesion and antibacterial activity of silver nanoparticles and graphene oxide-silver nanoparticle composites - Gómez de Saravia, Sandra Gabriela (2020)
The rise of nanotechnology has allowed the development of several inorganic nanoparticles with strong biocidal properties against bacteria, fungi, and viruses. Among them, silver nanoparticles (AgNPs) stand out as one of the most promising antimicrobial nanomaterials. Graphene oxide (GO) is another attractive nanomaterial with antimicrobial properties. Although the antimicrobial effect of AgNPs and GO is known, the development of hybrid materials of GO-AgNPs has considerable interest in various applications since they may exhibit synergistic bactericidal properties that exceed the yields of the individual components. The aims of this work were to evaluate the antimicrobial activity and anti-adhesion properties of AgNPs and GO-AgNPs nanocomposites for potential applications in antimicrobial coatings. The antimicrobial activity was tested by agar diffusion method. It was found that activity varied according to the synthesis procedure of the nanomaterials. Pseudomonas aeruginosa, Bacillus cereus and Kokuria rhizophila were the most susceptible strains. The nanocomposite GO- AgNPs synthetized using the ex-situ method exhibited the highest antibacterial activity against all the assayed strains. Similar results were obtained for bacterial adhesion inhibition tests. Thus, GO-AgNPs nanohybrids could be applied as antibacterial coatings to prevent bacterial biofilm development.